2017
DOI: 10.1371/journal.pone.0180498
|View full text |Cite
|
Sign up to set email alerts
|

Association of coping strategies with mortality and health-related quality of life in hemodialysis patients: The Japan Dialysis Outcomes and Practice Patterns Study

Abstract: BackgroundHemodialysis patients are exposed to disease- and treatment-related stresses, and use various coping strategies to deal with these stresses. Although some studies have reported the association of coping strategies with mortality or health-related quality of life (QOL) in some populations, the effect of coping strategies on clinical outcomes in hemodialysis patients remains unclear. We investigated the association in a longitudinal design among Japanese hemodialysis patients.MethodsWe examined Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
1
25
0
4
Order By: Relevance
“…Although both strategies bring about a reduction in stress, studies showed that those individuals who use emotion-focused coping strategies have lower psycho cognitive adaptation (41). Studies which investigated the relationship between coping strategies and quality of life in hemodialysis patients, emotion-focused coping showed a deteriorating effect on mental component of QOL in Japanese, Brazilian, and Iranian hemodialysis patients (15,42,43). In contrast with these studies, in this study emotion-focused coping strategies' total score was found to be lower in patients with depressive disorder and correlated with better QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Although both strategies bring about a reduction in stress, studies showed that those individuals who use emotion-focused coping strategies have lower psycho cognitive adaptation (41). Studies which investigated the relationship between coping strategies and quality of life in hemodialysis patients, emotion-focused coping showed a deteriorating effect on mental component of QOL in Japanese, Brazilian, and Iranian hemodialysis patients (15,42,43). In contrast with these studies, in this study emotion-focused coping strategies' total score was found to be lower in patients with depressive disorder and correlated with better QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Research on diabetes patients showed that the ways in which adolescents with type 1 diabetes cope with diabetes‐related stress predict quality of life and symptoms of depression . Also, emotion‐focused coping showed a deteriorating effect on mental health of Japanese and Brazilian hemodialysis patients …”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on the treatment-related stressors experienced and coping strategies used by patients on HD [2,[8][9][10][11][12]. In Tu et al [8]'s study, Taiwanese patients on HD aged 20-45 years were found to have high stress levels.…”
mentioning
confidence: 99%
“…In Kara [2]'s study, higher treatmentrelated stress levels were also associated with lower coping strategies in Turkish patients on HD [2]. Interestingly, in the Japan Dialysis Outcomes and Practice Patterns Study of 1,354 patients on HD, it was found that "problem-focused engagement" as coping strategies were associated with both longer survival and improvement in physical functioning and mental health [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation